Tunicamycin enhances the antitumor activity of trastuzumab on breast cancer in vitro and in vivo - Han, Xiqian (Oncotarget, 2015)
Trastuzumab, a humanized monoclonal antibody targeting HER2, has demonstrated clinical benefits for women with HER2-positive breast cancer; however, trastuzumab resistance remains the biggest clinical challenge. In this study, results showed that tunicamycin, an inhibitor of N-glycosylation, synergistically enhanced the antitumor activity of trastuzumab against HER2-overexpressing breast cancer cells through induction of cell cycle arrest and apoptosis. Combined treatment of tunicamycin with trastuzumab dramatically decreased the expression of EGFR family and its down signaling pathway in SKBR3 and MCF-7/HER2 cells. Tunicamycin dose-dependently inhibited tumor growth in both of SKBR3 xenografts and MCF-7/HER2 xenografts. Optimal tunicamycin without inducing ER stress in liver tissue significantly increased the antitumor effect of trastuzumab in MCF-7/HER2 xenografts. Combinations of trastuzumab with N-glycosylation inhibitors tunicamycin may be a promising approach for improving clinical efficacy of trastuzumab.